Effect of a single intra-articular administration of stanozolol in a naturally occurring canine osteoarthritis model: a randomised trial - J. C. Alves; A. Santos; P. Jorge; C. Lavrador; L. Miguel Carreira (Scientific Reports, 2022)
Abstract Osteoarthritis (OA) is a disease with a high negative impact on patient’s quality of life and a high financial burden. It is a source of chronic pain and affects all mammals, including humans and dogs. As the dog is a common model for translation research of human OA, and exploring spontaneous dog OA can improve the health and well-being of both humans and dogs. To describe the effect of the intra-articular administration of stanozolol in a naturally occurring canine OA model, forty canine (N = 40) hip joints were randomly assigned to receive stanozolol or saline (control). On treatment day and at 8, 15, 30, 90, and 180 days post-treatment, several evaluations were conducted: weight distribution, joint range of motion, thigh girth, digital thermography, and radiographic signs. Also, synovial fluid C-reactive protein and interleukin-1 levels were evaluated. Results from four Clinical Metrology Instruments was also gathered. Results were compared with Repeated Measures ANOVA, with a Huynh–Feldt correction, paired-samples t-test, or Wilcoxon signed-rank test, with p < 0.05. OA was graded as mild (90%), moderate (5%), and severe (5%), including both sexes. They had a mean age of 6.5 ± 2.4 years and a bodyweight of 26.7 ± 5.2 kg. No differences were found between groups at treatment day in all considered evaluations. Weight distribution showed significant improvements with stanozolol from 15 days (p < 0.05) up to 180 days (p < 0.01). Lower values during thermographic evaluation in both views taken and improved joint extension at 90 (p = 0.02) and 180 days (p < 0.01) were observed. Pain and function scores improved up to 180 days. In the control group, radiographic signs progressed, in contrast with stanozolol. The use of stanozolol was safe and produced significant improvements in weight-bearing, pain score, and clinical evaluations in a naturally occurring canine OA model.